2020
DOI: 10.1097/md.0000000000023706
|View full text |Cite
|
Sign up to set email alerts
|

Vestibulo-ocular reflex tests may reflect unilateral Ménière disease progression

Abstract: Vestibular disorders can manifest several patterns of horizontal vestibulo-ocular reflex (VOR) impairment, which can be detected by caloric test and video head impulse test (vHIT). Several studies have examined the patterns of caloric-vHIT response in Ménière disease (MD). The purpose of this study was to investigate the diversity of caloric-vHIT response and its related factors in unilateral MD patients. We also explore the possibility of assessing the progression of unilateral MD by using the horizontal VOR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…Similarly, Mateijsen et alalso found no relationship between MRI-PP distance and duration of disease in the MD patients [5]. In patients with MD, the results of EcochG and glycerol test can be used as traditional audiological indicators for ELH, and the caloric response is correlated with the severity of vestibular ELH (as demonstrated by gadoliniumenhanced MRI of the inner ear) [48], suggesting that caloric response may serve as a vestibular indicator for ELH [49]. These audio-vestibular variables may reflect the severity of MD indirectly and were not correlated with the radiological anatomical variations.…”
Section: No Correlation Between Mri-visualized Measurements and Clinical Features Or Audio-vestibular Findings In Deh And MDmentioning
confidence: 98%
“…Similarly, Mateijsen et alalso found no relationship between MRI-PP distance and duration of disease in the MD patients [5]. In patients with MD, the results of EcochG and glycerol test can be used as traditional audiological indicators for ELH, and the caloric response is correlated with the severity of vestibular ELH (as demonstrated by gadoliniumenhanced MRI of the inner ear) [48], suggesting that caloric response may serve as a vestibular indicator for ELH [49]. These audio-vestibular variables may reflect the severity of MD indirectly and were not correlated with the radiological anatomical variations.…”
Section: No Correlation Between Mri-visualized Measurements and Clinical Features Or Audio-vestibular Findings In Deh And MDmentioning
confidence: 98%
“…As for evaluating function of semicircular canal (SCC), the instrumental tests mainly include the caloric test and vHIT. It has been reported that MD patients tend to have a dissociated pattern of caloric-vHIT response ( McCaslin et al, 2015 ; Rubin et al, 2018 ; Zhou et al, 2020 ; Hannigan et al, 2021 ). The exact mechanism underlying this caloric-vHIT dissociation remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Nine 2 , 10 , 11 , 12 , 13 , 14 , 17 , 18 , 19 of the 12 articles analyzed showed caloric tests were performed with water (6 of the them at temperatures of 30 °C and 44 °C), 2 , 10 , 11 , 12 , 13 , 17 , 18 while in three of the studies air (at temperatures of 24 °C and 50 °C) 15 , 16 , 20 was used as a stimulus to perform the same test, which is equivalent when performed at these temperatures. 21 In 11 articles, labyrinthine predominance was used as a criterion for altering the caloric test, which varied between the values of ≥22% and ≥30%.…”
Section: Discussionmentioning
confidence: 99%